Process optimization of herbal tablet manufacturing using central composite design - Perete, Carlo L.
The objective of this research was to model the use of Quality Risk Management & Design of Experiments (DOE) for the local drug industry. This was achieved through the process optimization of an herbal tablet formulation of Orthosiphon aristatus (Blume) Miquel (Family Labiatae), one of the Philippine medicinal plants with diuretic activity, through the use of Failure Mode & Effect Analysis (FMEA) and Central Composite Design. The FMEA identified the critical process variables in relation to the desired physical characteristics of the herbal tablet. Following this identification, a central composite design was set-up to simultaneously study the effects of the critical process variables of granulation mixing time, starch paste concentration and granulation moisture content on the desired physical attributes of the herbal tablet; which are an optimal tablet disintegration time, hardness and friability. The quantified effects from the bulk in-process and compressed tablets were analyzed using the Statistica® software; which established the relationship of the selected process variables with the final tablet physical characteristics. The analysis also resulted to the selection of the optimum process variables for the herbal tablet manufacture in relation to the optimal physical tablet characteristics. The results were able to demonstrate the selection of the process critical control parameters, and indicate the linear and quadratic relationships of the process parameters with the final tablet physical characteristics.
Available to the general public.
Thesis (Master of Science in Industrial Pharmacy)--University of the Philippines Manila, November 2007.
Keywords: Tableting; Pharmaceutical industry -- Quality control